ARSITEKTUR SISTEM INFORMASI TERINTEGRASI UNTUK DATA JEMAAT LINGKUP REGIONAL PADA GEREJA X - Adi Suryaputra Paramita (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2022)
The development of technology presents challenges for non-profit organizations such as churches. Indirectly churches are required to be more organized and present accurate data and carry out an in-depth analysis of the condition of the church congregation. Church X has 40 local churches in regional areas spread across several East Java and Bali cities such as Surabaya, Malang, Kediri, Tuluagung, Sidoarjo, and Denpasar. In providing effective services to the local congregation, Church X needs to create an integrated information system for congregational data management and the information system used to see the current condition of the congregation in all local churches so that effective and targeted services can be carried out. In this study, an administrative information system model for integrated congregational data management in Church X will be designed, an information system designed to be web-based. It is easy to implement and does not require investment in expensive information and communication technology equipment. The integrated information system model will be built using microservices. Through this model, an Information System model will be obtained that can assist the process of collecting data on congregations in the regional church X while maintaining data privacy for each local church.